2020
DOI: 10.1002/jcop.22468
|View full text |Cite
|
Sign up to set email alerts
|

The role of the parent–child relationship in fostering resilience in American Indian/Alaskan Native children

Abstract: Resilience is a key characteristic to study in families, particularly those who have experienced significant systemic risk factors. While much resilience research focuses on ethnic and cultural minorities, little research focuses specifically on American Indian/Alaskan Native (AI/AN) families. The parent-child relationship has been demonstrated to be a key characteristic in families, and this relationship may also serve as a protective factor for AI/AN families. Positive parent-child relationships are consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
(47 reference statements)
0
2
0
1
Order By: Relevance
“…Decreased peer time and increased parental control during the pandemic operates in the opposite way of typical adolescent and young adult development, which is usually characterized by greater autonomy from parents and increased influence from peers (Steinberg & Silk, 2002). Parent-child relationship quality as evidenced earlier in life may moderate the link between experiencing stressful life events and changes in adjustment because supportive parent-child relationships may serve as a resource promoting resilience for both young people and their parents (Tolliver-Lynn et al, 2021). Thus, parent-adolescent relationship quality prior to the COVID pandemic may be expected to predict changes in adjustment during the pandemic for both parents and young adult children as well as to moderate links between disruption during the pandemic and changes in adjustment.…”
mentioning
confidence: 99%
“…Decreased peer time and increased parental control during the pandemic operates in the opposite way of typical adolescent and young adult development, which is usually characterized by greater autonomy from parents and increased influence from peers (Steinberg & Silk, 2002). Parent-child relationship quality as evidenced earlier in life may moderate the link between experiencing stressful life events and changes in adjustment because supportive parent-child relationships may serve as a resource promoting resilience for both young people and their parents (Tolliver-Lynn et al, 2021). Thus, parent-adolescent relationship quality prior to the COVID pandemic may be expected to predict changes in adjustment during the pandemic for both parents and young adult children as well as to moderate links between disruption during the pandemic and changes in adjustment.…”
mentioning
confidence: 99%
“…Dari hasil penelitian yang dilakukan oleh Utami (2021) menjelaskan bahwa hubungan pola asuh orang tua di rumah dengan perilaku anak, terutama pada kenakalan dan pengendalian diri pada remaja karena remaja merupakan masa peralihan dari anak-anak menuju dewasa dan sering terjadi konsep atau pemahaman yang salah tentang peran orang tua dan pola asuh orang tua terhadap remaja (Nur Utami & Raharjo, 2019). Kualitas hubungan antara orang tua dan anak yang kurang baik dapat berdampak pada mental anak, hal yang biasa terjadi adalah depresi pada anak serta kecemasan, yang bahkan hal tersebut jarang dilihat oleh orang tua yang nantinya berdampak pada kehidupan sosial anak di masa yang akan datang (Tolliver-Lynn et al, 2021). Sehingga dengan adanya permasalahan yang terjadi antara masyarakat lokal dan masyarakat transmigrant pada dasarnya perlu upaya orang tua untuk memberikan pemahaman kepada anak, terutama untuk meningkatkan persatuan di masa yang akan datang.…”
Section: Pendahuluanunclassified
“…Despite the massive historical traumatic events and current challenges experienced by American Indians, the dynamic of resilience cannot be ignored. Elders in one study identified individual, family, and community constructs that promote resilience as connectedness, culture, and spirituality ( 28 ); furthermore, as Tolliver-Lynn et al ( 29 ) relate, “many protective characteristics that promote resilience are deeply embedded in traditional AI/AN culture” ( 29 ). Elders in another study asserted that healing from said historical traumas involves reclamation of one's culture ( 9 , 30 ).…”
Section: Introductionmentioning
confidence: 99%